The Diurnal Cooling Effect of Green Space Structure on the Summer Urban Thermal Environment From a High-Resolution Perspective - Shihao Wang; Chaoyang Sun; Lin Huang; Huading Shi; Xinliang Xu; Dongrui Han; Qingbao Gu; Hanbing Liu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Urban thermal environment (UTE) issue has reduced the quality of life for residents, and urban green spaces (UGs) can effectively improve the UTE. However, at a fine scale, the cooling capacity of UGs with different structures and the diurnal variation still require in-depth study. This article, based on land use, vegetation cover, ground elevation, anthropogenic heat emission, and meteorological data, utilizes the UrbClim model to simulate high-resolution hourly air temperature (Ta) in Tianjin's urban area during summer high-temperature days. It analyzes the structural characteristics of UGs at a fine scale and reveals the diurnal cooling effect variations among UGs with various structures. The results indicate that the Urban Heat Island (UHI) within Tianjin's urban area consists of a primary heat island and several smaller heat islands scattered around it. The northern part experiences higher Ta, while the southeastern part is cooler, with the highest daytime Ta ranging from 30.7 to 34.2 °C and the lowest nighttime Ta ranging from 26.0 to 31.7 °C. The structure of UGs significantly influences the spatial pattern and fluctuation of Ta. UGs with high coverage show a diminished cooling effect at night and can reduce the extent of daily Ta fluctuations, particularly when the greenery exceeds 80%, where the effect is most pronounced. The Ta stability of patchy and aggregated UGs is stronger than that of linear and scattered UGs. Vegetation types have different regulatory effects on diurnal Ta; during the day, trees have a more significant cooling effect than grasslands, while at night, this cooling effect is attenuated. Furthermore, the cooling benefits were amplified during extreme heat days. At the hottest time of the day, UGs with a high percentage of area, patchy and aggregated shape, and tree vegetation type have the best cooling effect, while at the coldest time of the night, these UGs slow down the dissipation of heat accumulated during the day and have a significant attenuation of the cooling effect. Our findings underscore the intricate relationships between the cooling effects and landscape structure of UGs, thereby aiding in the formulation of urban planning strategies to maximize the cooling benefits.